TO THE KNOWLEDGE OF POORLY KNOWN CARABIDS (COLEOPTERA, CARABIDAE) OF THE CASPIAN LOWLAND - I. A. Belousov; I. I. Kabak; G. M. Abdurakhmanov; G. M. Nakhibasheva (Юг России: экология, развитие)
New data are given on the distribution of the carabids Clivinopsis conicicollis Reitter and Anaulacus (Aephnidius) ruficornis Chaudoir in the Caspain Lowland . Photographs of both species are provided and their distribution is mapped. C. conicicollis is for the first time recorded for Daghestan while members of the genus Anaulacus were not previously known for Russia, Azerbaidjan, Iran, and Turkmenistan. A determination key is given to distinguish between species of the genus Anaulacus and members of the related genus Masoreus Dejean.